Revisiting the patriarchal bargain: The intergenerational power dynamics of household money management in rural Nepal. (December 2018) - Gram, Lu; Skordis-Worrall, Jolene; Mannell, Jenevieve; Manandhar, Dharma S.; Saville, Naomi; Morrison, Joanna
Highlights: We analyzed the intergenerational power dynamics of money management in rural households in contemporary Nepal. We found that junior wives and husbands often became secret allies in seeking financial autonomy from their in-laws. Intergenerational power relations may be just as important as male-female power relations for women's economic empowerment. Abstract: Although power struggles between daughters-in-law and mothers-in-law in the South Asian household remain an enduring theme of feminist scholarship, current policy discourse on 'women's economic empowerment' in the Global South tends to focus on married women's power over their husband; this neglects intergenerational power dynamics. The aim of this study was to describe and analyze the processes involved in young, married women's negotiations of control over cash inside the extended household in a contemporary rural Nepali setting. We conducted a grounded theory study of 42 households from the Plains of Nepal. Our study uncovered multiple ways in which junior wives and husbands in the extended household became secret allies in seeking financial autonomy from the rule of the mother-in-law to the wife. This included secretly saving up for a household separation from the in-laws. We argue these secret financial strategies constitute a means for junior couples to renegotiate the terms of Kandiyoti's (1988) 'patriarchal bargain' wherein junior wives traditionally had to accept subservience to their husband and mother-in-law in exchange for economic security and eventual authority over their own daughters-in-law. Researchers, activists and policy-makers concerned with women's economic empowerment in comparable contexts should consider the impact of intergenerational power relations on women's control over cash.